Laboratory evidence for slip evolution of granite fractures due to chemical stimulation in geothermal reservoirs - Wu, Wei (2022)
Understanding the mechanisms of injection-induced seismicity is critical for managing the anthropogenic geohazard, which recently hinders the development of geothermal energy. Here we reanalyzed the seismic data recorded during the acid fluid injection at the geothermal field of Soultz-sous-Forêts (France) in 2005 and conducted a series of water injection experiments on granite fractures treated with dilute hydrochloric acid. We aimed to provide laboratory evidence for slip transition of the chemically treated fractures in geothermal reservoirs. We found that the amount of induced seismic events is promoted by the acid treatment, and the distribution of these seismic events is expanded in the post-acid water injection. Our experimental study demonstrated non-linear distributions of water pressure and frictional strength over the fracture during the water injection. The ratio of the shear stress variation to the fluid pressure variation reduces with a larger aseismic slip front amplification factor, which reflects the transition from the aseismic to seismic slip. The study revealed that the acid treatment potentially causes an increase in seismic event amount but a reduction in moment magnitude in the chemically treated region. The aseismic slip in the treated region may promote shear stress gradient along the fracture and result in the seismic events expanding in untreated regions. Additionally, the moment magnitude may be amplified when the fracture dictates neighboring fractures beyond the treated region.